Association of Chemotherapy Timing in Pregnancy With Congenital Malformation - van Gerwen, Mathilde; Maggen, Charlotte; Cardonick, Elyce; Verwaaijen, Emma J; van den Heuvel-Eibrink, Marry; Shmakov, Roman G; Boere, Ingrid; Gziri, Mina M; Ottevanger, Petronella B; Lok, Christianne A R; Halaska, Michael; Shao, Long Ting; et al. (JAMA network open, 2021)
IMPORTANCE: Chemotherapy during the first trimester of pregnancy should be avoided owing to the risk of congenital malformations. However, the precise gestational age at which chemotherapy can be initiated safely remains unclear. OBJECTIVE: To assess congenital malformation rates associated with gestational age at initiation of chemotherapy among pregnant women with cancer. DESIGN, SETTING, AND PARTICIPANTS: This multicenter cohort study evaluated all pregnant women who received chemotherapy between 1977 and 2019 registered in the International Network on Cancer, Infertility and Pregnancy (INCIP) database. Data were analyzed from February 15 to June 2, 2020. EXPOSURES: Cancer treatment with chemotherapy during pregnancy. MAIN OUTCOMES AND MEASURES: Analysis was focused on major and minor structural malformations in offspring, defined by EUROCAT, detected during pregnancy or at birth. RESULTS: A total of 755 women in the INCIP database who underwent cancer treatment with chemotherapy during pregnancy were included in analysis. The median (range) age at cancer diagnosis was 33 (14-48) years. Among offspring, the major congenital malformation rate was 3.6% (95% CI, 2.4%-5.2%), and the minor congenital malformation rate was 1.9% (95% CI, 1.0%-3.1%). Chemotherapy exposure prior to 12 weeks gestational age was associated with a high rate of major congenital malformations, at 21.7% (95% CI, 7.5%-43.7%; odds ratio, 9.24 [95% CI, 3.13-27.30]). When chemotherapy was initiated after gestational age 12 weeks, the frequency of major congenital malformations was 3.0% (95% CI, 1.9%-4.6%), which was similar to the expected rates in the general population. Minor malformations were comparable when exposure occurred before or after gestational age 12 weeks (4.3% [95% CI, 0.1%-21.9%] vs 1.8% [95% CI, 1.0-3.0]; odds ratio, 3.13 [95% CI, 0.39-25.28]). Of 29 women who received chemotherapy prior to 12 weeks gestation, 17 (58.6%) were not aware of pregnancy, and 6 (20.7%) experienced a miscarriage (3 women [10.3%]) or decided to terminate their pregnancy (3 women [10.3%]). CONCLUSIONS AND RELEVANCE: This cohort study found that chemotherapy was associated with an increased risk of major congenital malformations only in the first 12 weeks of pregnancy. The risk of congenital malformations when chemotherapy was administered during the first trimester and the high number of incidental pregnancies during cancer treatment in the INCIP registry underscore the importance of contraceptive advice and pregnancy testing at the start of chemotherapeutic treatment in young women with cancer.
Keywords: Pregnancy; gestační stáří; Abnormalities, Drug-Induced; Time Factors; lidé středního věku; Odds Ratio; abnormality vyvolané léky; vývoj plodu; protinádorové látky; Cohort Studies; odds ratio; Drug Administration Schedule; Pregnant People; časové faktory; Humans; Middle Aged; těhotné ženy; Antineoplastic Agents; Female; kohortové studie; mladiství; první trimestr těhotenství; ženské pohlaví; Fetal Development; rozvrh dávkování léků; Pregnancy Trimester, First; Neoplasms; Gestational Age; mladý dospělý; Adult; Young Adult; Adolescent; dospělí; lidé; těhotenství; nádory